2021
DOI: 10.1371/journal.pone.0248150
|View full text |Cite
|
Sign up to set email alerts
|

β-Sitosterol 3-O-D-glucoside increases ceramide levels in the stratum corneum via the up-regulated expression of ceramide synthase-3 and glucosylceramide synthase in a reconstructed human epidermal keratinization model

Abstract: β-Sitosterol 3-O-d-glucoside (BSG) is known to act as an agonist by binding to estrogen receptors, and estrogen has been reported to enhance the activity of β-glucocerebrosidase, an epidermal ceramide metabolizing enzyme. In this study, we determined whether BSG up-regulates ceramide levels in the stratum corneum (SC) of a reconstructed human epidermal keratinization (RHEK) model. Treatment with BSG significantly increased the total ceramide content by 1.2-fold compared to that in the control in the SC of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…On the other hand, only a single clinical study has reported the beneficial effects of rice GlcCer [16]. The ingestion of rice-derived GlcCer has been shown to enhance skin ceramide production [22], particularly ceramide [EOS], which exerts stronger hydrating effects among ceramide species [42]. As the underlying mechanism, we confirmed that BSG enhanced the production of ceramide synthase-3 and glucosylceramide synthase [22].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the other hand, only a single clinical study has reported the beneficial effects of rice GlcCer [16]. The ingestion of rice-derived GlcCer has been shown to enhance skin ceramide production [22], particularly ceramide [EOS], which exerts stronger hydrating effects among ceramide species [42]. As the underlying mechanism, we confirmed that BSG enhanced the production of ceramide synthase-3 and glucosylceramide synthase [22].…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, BSG may be digested and absorbed from the gut and alter epidermal hydration similar to cholesterol and ceramides. Secondly, we recently demonstrated that BSG increased ceramides in the s. corneum of a human epidermal equivalent by enhancing the de novo ceramide synthesis pathway [22]. Based on these findings about dietary supplemented GlcCer and an in vitro study of BSG, we hypothesized that the combination of GlcCer and BSG is an appropriate composition for effectively improving epidermal dehydration.…”
Section: Introductionmentioning
confidence: 96%
“…Lycoperoside H ( 3 ) is the most abundant saponin in TSE, and its concentration-dependent effect (1 and 10 µM) was observed in ceramide production. Our previous studies demonstrated that tiliroside isolated from strawberry seeds increases the ceramide (NS, NDS) contents [ 32 ], and β-sitosterol 3- O -glucoside isolated from rice bran increased ceramide (EOS) [ 44 ]. On the other hand, the present study demonstrated that lycoperoside H ( 3 ) increased ceramide (NP), which was not observed in tiliroside and β-sitosterol 3- O -glucoside.…”
Section: Discussionmentioning
confidence: 99%
“…The separated SC samples were washed with PBS and stored at −80 °C until the determination of ceramides. The extraction method described in previous studies [ 32 , 44 ] was used for lipid extraction. Namely, the SC samples were homogenized with an ultrasonic homogenizer (AGC Techno Glass Co., Ltd. Shizuoka, Japan) in a 4 mL mixture of chloroform, methanol, and PBS (1:2:0.8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation